Study the correlation of iodine nutrition and autoimmunity among Euthyroid goiter patient in a tertiary care hospital in Tamil Nadu - Pichandi, Suresh; Sivakumar, J; Janakiraman, P; Ramadevi, K (Asian Journal of Medical Sciences, 2022)
Background: Iodine is an essential micronutrient for the thyroid hormone synthesis. It is crucial for the growth and development of human life. Deficient or excessive iodine intake may affect thyroid gland size and functions. Despite the intake of iodized salt, the increasing occurrence of thyroid disorders in India. Aim and Objective: Aim of the present study is to analyse the nutritional status of iodine among Euthyroid goiter patient by measuring urinary excretion and correlate with thyroid hormone and auto antibodies Materials and Methods: one hundred and fifty Euthyroid goiter patients and one hundred and fifty age-matched normal adult were included in study. Urinary Iodine level and serum TSH, freeT4, freeT3, AMA and ATG were estimated both case and control groups. Results: The mean urinary iodine excretion concentration (UIC) in Euthyroid goiter patient was 244.39 µg/L and excess urinary iodine excretion was found in 48%. There were elevated serum AMA levels in Euthyroid goiter patient and that positive correlated with excess iodine. Conclusion: In this study we found that excess urinary iodine excretion among patients. This study we observed iodine excess associated complications, viz., benign goiter (49%), thyroiditis (24%), cancer of thyroid (21%) and thyrotoxicosis (6%).